Large‐Scale Analysis of Age and Sex Effects on Corrected QT and JT Intervals: Insights From Hospital‐Based Controls and Moxifloxacin‐Treated Cases - Eunwoo Kim; Hyun Young Lee; Young‐Min Ye; Anhye Kim (Clinical and Translational Science)
ABSTRACT The corrected QT (QTc) interval is a critical marker for assessing proarrhythmic potential in drug development, while the corrected JT (JTc) interval provides specific insight into ventricular repolarization. This study quantitatively analyzed the relationships of QTc and JTc intervals with age and sex utilizing a large real‐world dataset of hospital‐based controls and moxifloxacin‐treated patients. This retrospective study analyzed 1,039,550 electrocardiograms and associated clinical data extracted from a previously constructed electrocardiogram database, categorizing cases as hospital‐based controls (n = 119,882) or moxifloxacin‐treated (n = 1586) based on predefined criteria. We observed a general trend of QTc and JTc interval prolongation with age in both groups, with moxifloxacin‐treated cases showing longer QTc and JTc intervals than hospital‐based controls. Multiple linear regression analysis indicated that in hospital‐based controls, QTc and JTc intervals increased with age, with males exhibiting shorter intervals than females. Meanwhile, in moxifloxacin‐treated cases, QTc and JTc intervals showed similar age‐dependent increases, although no significant sex differences were observed in the QTc interval. Therefore, this study quantified the effects of age and sex on QTc and JTc intervals in hospital‐based controls and highlighted similar age‐related trends in moxifloxacin‐treated cases, underscoring the relevance of age and sex as key factors in interpreting QTc and JTc intervals across diverse clinical contexts.